Critical thinking levels of nursing students: analysis from the application of the virtual simulator Health Simulator (Research, Society and Development, 2022)
Critical thinking is characterized by being a thought that seeks to prove a point, interpret what something means and/or solve a problem. The general objective of this research was to identify the levels of critical thinking of nursing students from the application of a virtual simulator, as well as to verify the students' perspective regarding their level in this category. This is a cross-sectional study, with a quantitative approach, carried out with 40 students at a university in southern Brazil. Critical thinking levels were statistically significant (p=0.001): Full was not identified by the simulator or by the students; Sufficient, one (2.5%) was verified in the simulator, and two (5%) students think they are in this category; Deficit, 14 (35%) in the simulator and 27 (67.5%) perceive to be in this degree; Insufficient, 18 (45%) by the simulator and 11 (27.5%) believe they are in this division; Severo, seven (17.5%) were identified by the simulator, although none of the students perceived themselves at this level. It is concluded that students have knowledge gaps regarding some elements that structure critical thinking, requiring the teaching of these skills, which, when involving critical thinking, favor the construction of student competencies.